2017
DOI: 10.1002/adma.201606945
|View full text |Cite
|
Sign up to set email alerts
|

Earth‐Abundant Chalcogenide Photovoltaic Devices with over 5% Efficiency Based on a Cu2BaSn(S,Se)4 Absorber

Abstract: In recent years, Cu ZnSn(S,Se) (CZTSSe) materials have enabled important progress in associated thin-film photovoltaic (PV) technology, while avoiding scarce and/or toxic metals; however, cationic disorder and associated band tailing fundamentally limit device performance. Cu BaSnS (CBTS) has recently been proposed as a prospective alternative large bandgap (~2 eV), environmentally friendly PV material, with ~2% power conversion efficiency (PCE) already demonstrated in corresponding devices. In this study, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
181
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(196 citation statements)
references
References 43 publications
14
181
1
Order By: Relevance
“…In 2012, Chen et al reported a low formation energy for Cu Zn +Sn Zn and 2Cu Zn +Sn Zn in kesterites and also proposed their deleterious role of introducing deep defects and bandgap narrowing. [6,9,11,[20][21][22][23] Here, we study the role of the proposed performance-limiting defects Cu Zn +Zn Cu and 2Cu Zn +Sn Zn by systematically substituting cations in Cu 2 ZnSnS 4 as characterized by both experimental and theoretical methods. [19] Hence, based on theoretical calculations, the possible performance-limiting point defects in kesterites are proposed to be the Cu-Zn antisite Cu Zn +Zn Cu , and the deep-trap-level-inducing Sn-antisite 2Cu Zn +Sn Zn .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Chen et al reported a low formation energy for Cu Zn +Sn Zn and 2Cu Zn +Sn Zn in kesterites and also proposed their deleterious role of introducing deep defects and bandgap narrowing. [6,9,11,[20][21][22][23] Here, we study the role of the proposed performance-limiting defects Cu Zn +Zn Cu and 2Cu Zn +Sn Zn by systematically substituting cations in Cu 2 ZnSnS 4 as characterized by both experimental and theoretical methods. [19] Hence, based on theoretical calculations, the possible performance-limiting point defects in kesterites are proposed to be the Cu-Zn antisite Cu Zn +Zn Cu , and the deep-trap-level-inducing Sn-antisite 2Cu Zn +Sn Zn .…”
Section: Introductionmentioning
confidence: 99%
“…[1] These solar-cell technologies are already commercialized, with lab-scale photovoltaic efficiencies exceeding 22%. [4,6,8,9] The extent to which these factors individually affect the photovoltaic performance is debated, but their ubiquity among kesterite absorbers indicates the presence of a large density of point defects. [3] Although the dominant limiting factors for this low performance are a matter of considerable discussion, [4] the following observations are consistent among kesterite absorbers: i) a low photoluminescence quantum yield (PLQY) and a short chargecarrier lifetime, [5] ii) a high value of Urbach band tail energy (larger than 30 meV for S-rich kesterites) and lack of a steep absorption onset, [6,7] and iii) the presence of secondary phases.…”
mentioning
confidence: 99%
“…[13] Further improvements in this direction need suitable bandgap materials for efficient absorption and carrier generation. Recently, Shin et al [14] demonstrated a solar cell of 5.2% PCE with Cu 2 BaSnS 4Àx Se x (CBTSSe) whose bandgap can be in the range of %1.6-2.0 eV [15] making it suitable for the top cell of a triple junction chalcogenide solar cell. Therefore, in this work, we propose a triple junction solar cell in which CBTSSe (bandgap %1.9 eV at x ¼ 1 [14] ), CZTS (bandgap %1.45 eV [16] ), and silver (Ag) mixed, CZTSe (ACZTSe, bandgap %0.97 eV [17] ) act as the primary absorbing layers of top, middle and bottom cells, respectively.…”
mentioning
confidence: 99%
“…As a result, current density falls significantly with the higher thickness of CZTS (Figure 2(a)) because of the reduced optical power absorption in the bottom cell. Thus, higher thickness of [19] 7 [18] 8.5 [17] 7 [16] Band gap (eV) 1.9 [14] 1.45 [18] 0.97 [17] 0.9 [16] Electron affinity (eV) 3.6 [19] 4.1 [24] 4.05 [17,25] 4.05 [13] Electron effective mass (m e /m o ) 0.37 [14,15] 0.18 [13,16] 0.08 [17] 0.07 [13,16] Hole effective mass (m p /m o ) 1.68 [14] 2 [13,16] 0.3 [17] 0.2 [13,16] Electron mobility (cm 2 V À1 s À1 ) 3 0 [26] 40 [21,24] 75 [23] 145 [13,21] Hole mobility (cm 2 V À1 s À1 ) 1 0 [27] 25 [21] 1 [17,23] 35 [13,21] Acceptor concentration (cm…”
mentioning
confidence: 99%
See 1 more Smart Citation